Influence of Push and Pull Factors on Loyalty Through Satisfaction in Managing Sustainable Tourism at Perancak Village, Bali - Gusti Ngurah Joko Adinegara; I Ketut Sirna (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The dynamic development of the tourism industry, particularly rural tourism, requires innovative and adaptive measures in managing tourist attractions and addressing the impact of changes in consumer leisure behavior. Rural tourism villages should offer unique features to attract tourists by maximizing services to ensure satisfaction.Purpose: This study aims to understand the impact of push and pull factors on tourist satisfaction, revisit intention and word-of-mouth, with customer satisfaction as a mediator at Perancak Tourism Village.Design/methodology/approach: This study employed a survey method to gather data from 99 tourists in Perancak Village and then analyzed the data using descriptive statistical analysis and PLS SEM to examine the relationships among variables. Findings/Result: The findings reveal that push factors did not have a significant effect on customer satisfaction, while pull factors had a significant effect on satisfaction. Satisfaction had a significant effect on revisit intention and word of mouth. Customer satisfaction has a significant influence based on pull factors on the intention to revisit and word of mouth. However, satisfaction did not significantly mediate push factors on revisit intention and word of mouth. These results prove that the attractiveness of rural tourism has an impact on tourist satisfaction and loyalty.Conclusion: This study highlights the potential significance of tourist attractions of customer satisfaction and behavior within the tourism context. Rural tourism management is expected to always demonstrate excellence and uniqueness to customers in attracting and retaining tourists so that tourist villages remain a priority for tourism.Originality/value (State of the art): The study's findings contribute to marketing research by integrating satisfaction as a mediating variable between motivation and loyalty to rural tourism destinations. This broadens the understanding of how attraction and push factors contribute to satisfaction and loyalty. Additionally, it offers valuable insights for rural tourism managers, particularly in Bali, in enhancing the potential of tourist attractions by managing the uniqueness of tourism to encourage innovation and sustainability. Keywords: push factor, pull factor, satisfaction, revisit intention, word of mouth